Subcutaneous and visceral fat are associated with worse outcomes in gunshot injuries but not stab injuries to the torso - Christopher Mejias; Mark Hoegger; Jason Snyder; Constantine Raptis; Vincent Mellnick (Trauma Surgery & Acute Care Open)
Purpose The effect of obesity in penetrating trauma outcomes is poorly understood. The purpose of this study was to determine if there is a protective effect of subcutaneous or visceral fat from stab and gunshot wounds.Methods 443 patients admitted after penetrating traumatic injury of the torso were retrospectively identified from our institution’s trauma registry. CT scans performed at presentation were used to determine cross-sectional area of visceral and subcutaneous fat at the level of the umbilicus via manual segmentation. Obesity-associated parameters including body mass index, visceral and subcutaneous fat were compared with injury severity score, length of hospital/intesive care unit (ICU) stay, and number of operating room (OR) visits. Parameters were compared between patients who sustained stab wounds versus gunshot injuries.Results Comparing all patients with gunshot injuries with those with stab injuries, gunshots resulted in increased hospital and ICU length of stay, and injury severity score (ISS). For patients with gunshot wounds, all obesity-related parameters correlated with increased length of stay and total ICU stay; subcutaneous fat and visceral fat were correlated with increased OR visits, but there was no significant correlation between obesity-related parameters and ISS. In contrast, with stab wounds there were no statistically significant associations between obesity parameters and any of the outcome measures.Conclusion For penetrating trauma in the torso, obesity is correlated with worse outcomes with gunshot injuries but not in stab injuries.Level of evidence Level III, prognostic and epidemiological.